Drainage Analysis of the West Outer Ring Road Surabaya - Danayanti Azmi Dewi Nusantara; Feriza Nadiar; Nastasia Festy Margini (Litbang Pemas - Universitas Islam Lamongan, 2023)
The development of West Outer Ring Road, abbreviated as JLLB, to improve the quality of infrastructure in the City of Surabaya. A breakthrough is needed by opening a new existing road section to break down traffic jams that lead to the main corridor section of the central city. The JLLB area, originally a green open area, was converted into a road area. This condition will cause changes in the sum of rainwater runoff that occur. The JLLB also intersects with the railroad tracks. A drainage system plan to ensure no puddles on the road, even through the railroad tracks. The method of this study follows hydrological and hydraulics analysis of the drainage systems. The results of drainage analysis on West Outer Ring Road, abbreviated as JLLB, there are several typical canal dimensions needed. All velocities can be controlled in the range of permissible velocity. The minimum velocity is 0,4 m/sec, and the maximum is 0,873 m/sec. The maximum planned discharge is 1,381 m3/sec. The capacity of boezem is planned to suit 5,104 hr of rain duration. Based on all that results, the drainage analysis of JLLB would be great if implemented according to plan.